2021
DOI: 10.3389/fgene.2020.606222
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Landscape Heterogeneity Matter: Responses of Neutral Genetic Diversity and Adaptive Traits in a Neotropical Savanna Tree

Abstract: Plants are one of the most vulnerable groups to fragmentation and habitat loss, that may affect community richness, abundance, functional traits, and genetic diversity. Here, we address the effects of landscape features on adaptive quantitative traits and evolutionary potential, and on neutral genetic diversity in populations of the Neotropical savanna tree Caryocar brasiliense. We sampled adults and juveniles in 10 savanna remnants within five landscapes. To obtain neutral genetic variation, we genotyped all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 117 publications
1
0
0
Order By: Relevance
“…The retention of semi-natural habitats has been shown to provide benefits for maintaining landscape heterogeneity and ecosystem services in arable land systems [7,8,11,31,32]. This study found that maintaining a 5% proportion of semi-natural habitats is the minimum threshold for achieving high landscape heterogeneity in arable land systems (Figure 3), which is in agreement with the recommended minimum share for Ecological Focus Areas (EFAs) established in the current CAP for arable farms [33].…”
Section: Discussionsupporting
confidence: 82%
“…The retention of semi-natural habitats has been shown to provide benefits for maintaining landscape heterogeneity and ecosystem services in arable land systems [7,8,11,31,32]. This study found that maintaining a 5% proportion of semi-natural habitats is the minimum threshold for achieving high landscape heterogeneity in arable land systems (Figure 3), which is in agreement with the recommended minimum share for Ecological Focus Areas (EFAs) established in the current CAP for arable farms [33].…”
Section: Discussionsupporting
confidence: 82%